2010
DOI: 10.1103/physreve.81.021121
|View full text |Cite
|
Sign up to set email alerts
|

Quantum persistence: A random-walk scenario

Abstract: In this paper we extend the concept of persistence, well defined for classical stochastic dynamics, to the context of quantum dynamics. We demonstrate the idea via quantum random walk and a successive measurement scheme, where persistence is defined as the time during which a given site remains unvisited by the walker. We also investigated the behavior of related quantities, e.g., the first-passage time and the succession probability (newly defined), etc. The study reveals power-law scaling behavior of these q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…The quantum renewal equation (17) and the Z transforms Eqs. (36,37) give a rather general relation between the amplitude of first detection φ n and the wave function of the system free of measurement |ψ f . In that sense the problem of first detection reduces to the solution of the Schrödinger equation, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantum renewal equation (17) and the Z transforms Eqs. (36,37) give a rather general relation between the amplitude of first detection φ n and the wave function of the system free of measurement |ψ f . In that sense the problem of first detection reduces to the solution of the Schrödinger equation, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The recent advance of single particle quantum tracking and measurement, for systems where coherence is maintained for relatively long times, is clearly a reason to be optimistic with respect to possible first detection measurements. Such measurements could test our predictions as well as those of a variety of other theoretical approaches [14,23,[31][32][33][34][35][36][37][38], some of which are compared with our results towards the end of this manuscript.…”
Section: Introductionmentioning
confidence: 86%
“…But for CCM, the direction reversal probability f is greater than 1/2 for all λ < 1 and f → 1/2 for λ → 1. Through further analysis of time correlation and other relevant quantities it was shown that direction reversal is preferred in these cases [51]. In the equivalent picture of the walk in the abstract space for gains and losses, it is similar to the fact that here individuals has a tendency to make a gain immediately after a loss and vice versa.…”
Section: Antipersistence Effect In Cc/ccm Walkmentioning
confidence: 80%
“…It was also shown in [51] that the "antipersistence effect" is maximum for no saving and decreases with saving. This is perhaps in tune with the human feeling of security associated with the saving factor.…”
Section: Antipersistence Effect In Cc/ccm Walkmentioning
confidence: 99%
See 1 more Smart Citation